2020
DOI: 10.3748/wjg.v26.i41.6455
|View full text |Cite
|
Sign up to set email alerts
|

Real-world cost-effectiveness associated with infliximab maintenance therapy for moderate to severe Crohn’s disease in China

Abstract: BACKGROUND Infliximab was the first approved biologic treatment for moderate to severe Crohn’s disease (MS-CD) in China. However, the cost-effectiveness of infliximab maintenance therapy (IMT) for MS-CD relative to conventional maintenance therapy remained unclarified. AIM To assess the cost-effectiveness of IMT for MS-CD in Chinese patients from the perspective of Chinese public insurance payer. METHODS A cohort of MS-CD patients managed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…After removing duplicates, we screened 226 records and assessed 138 full-text articles based on inclusion and exclusion criteria. Eventually, 92 pharmacoeconomic evaluations were included in the review and underwent data extraction (figure 1), detailed information on included studies can be found in online supplemental table 2 19–110…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, we screened 226 records and assessed 138 full-text articles based on inclusion and exclusion criteria. Eventually, 92 pharmacoeconomic evaluations were included in the review and underwent data extraction (figure 1), detailed information on included studies can be found in online supplemental table 2 19–110…”
Section: Resultsmentioning
confidence: 99%
“…Real-world research is rooted in clinical practice and comes from a wide range of sources, including hospitalization records, laboratory examination, images, and follow-up records during diagnosis and treatment. There were multiple studies based on real-world evidence demonstrating effectiveness and economy of different drugs, such as erenumab for headache, infliximab for Crohn disease, and apatinib for metastatic colorectal cancer ( Gou et al, 2018 ; Kanaan et al, 2020 ; Shi et al, 2020 ). Our aims were to explore the effectiveness and economy of PPC in patients with liver diseases based on real-world research, compare it with other hepatoprotective drugs (alone or combination medication), and evaluate the application of PPC in specific-disease cohorts, in order to optimal regimen therapy in clinical to treat hepatopathies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the disease activity may be uncontrolled even under the administration of these above‐mentioned treatments, which require monoclonal antibodies to further control the symptoms 2,6 . Infliximab is the first biologic approved for CD treatment in China, which has comparable therapeutic efficacy to other TNF inhibitors, higher practical value, and lower costs for CD patients 7–9 . However, since only 40%–50% of CD patients would respond to infliximab treatment, their clinical outcomes remain miserable 8,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Infliximab is the first biologic approved for CD treatment in China, which has comparable therapeutic efficacy to other TNF inhibitors, higher practical value, and lower costs for CD patients [7][8][9] . However, since only 40%-50% of CD patients would respond to infliximab treatment, their clinical outcomes remain miserable 8,10,11 .…”
Section: Introductionmentioning
confidence: 99%